Type designation and new combination for the alpine intergeneric hybrid ×Pseudadenia micrantha (Orchidinae, Orchidaceae) - Oddone, Luca; Bongiorni, Luciano; Casabianca, Angelo (Phytotaxa, 2014)
A new combination, ×Pseudadenia micrantha, is proposed for the rare intergeneric hybrid between Gymnadenia rhellicani × Pseudorchis albida. Kerner did not designate a holotype and the 1976 typification of Hautzinger was not in accord with the ICN Code. An illustration by Kerner is designated here as the lectotype. Chorological and morphological notes detailing comparison with the parental species are provided. Una nuova combinazione, ×Pseudadenia micrantha, viene proposta per il raro ibrido intergenerico tra Gymnadenia rhellicani × Pseudorchis albida. Kerner non istituì un olotipo e la tipificazione fatta da Hautzinger nel 1976 è contro il Codice ICN. Una illustrazione di Kerner viene designata come lectotipo. Vengono fornite anche note corologiche e morfologiche di confronto con le specie parentali.